Association of serum arginase I with L-arginine, 3-nitrotyrosine, and exhaled nitric oxide in healthy Japanese workers. (February 2014) - Ogino, K.; Wang, D. H.; Kubo, M.; Obase, Y.; Setiawan, H.; Yan, F.; Takahashi, H.; Zhang, R.; Tsukiyama, Y.; Yoshida, J.; Zou, Y.
Abstract: The associations of serum arginase I with serum L-arginine, serum 3-nitrotyrosine, and fractional exhaled nitric oxide (FENO) were evaluated cross-sectionally in healthy Japanese workers. The serum median (minimum–maximum) levels of arginase I, 3-nitrotyrosine, and FENO in healthy people (n = 130) were 14.6 (0.94–108.1) ng/mL, 81.0 (0.27–298.6) pmol/mg protein, and 14.0 (5.0–110.0) parts per billion, respectively. Significant correlations of arginase I with FENO, L-arginine, 3-nitrotyrosine, and percent predicted forced expiratory volume in 1 s (FEV1 (% predicted)) were observed, and correlations of FENO with immunoglobulin E (IgE), NOx, arginase I, and sex and allergy were also observed. By multiple regression analysis, arginase I showed positive associations with FENO and 3-nitrotyrosine, and a negative association with L-arginine; and FENO showed positive associations with IgE and NO2 − + NO3 − (NOx), and a negative association with L-arginine, as well as an association with sex. Moreover, logistic regression analysis showed linear inverse associations of arginase I and 3-nitrotyrosine with L-arginine, and showed linear positive associations of FENO with IgE and NOx. It was concluded that serum arginase I might regulate serum L-arginine and 3-nitrotyrosine via L-arginine, and that IgE or NOx might regulate FENO in a healthy Japanese population.